Ambivalence and Recursion in Castlevania: Symphony of the Night - Martin, Paul (Eludamos: Journal for Computer Game Culture, 2011)
This article is a close reading of Castlevania: Symphony of the Night (KCE Tokyo, 1997) that offers its various forms of recursion as performed by the player, the character and the plot as means of enriching the characterisation of the protagonist, Alucard, as ambivalent. It draws on theories of the labyrinth as a way of enacting a meaningful routine to illustrate this relationship between space, performance and meaning in the game.